European firm adjustment during times of economic crisish - Silvia Fabiani; Ana Lamo; Julián Messina; Tairi R\~o\~om (IZA Journal of Labor Policy, 2015)
This paper exploits a unique cross-country, firm-level survey to study the responses of European firms to the sharp demand and credit contraction triggered by the global Great Recession of 2009. The analysis reveals that cost reduction-particularly labour cost reduction through the adjustment of quantities rather than prices-was the prevailing strategy that firms had adopted by summer 2009. Remarkably, not even during the worst postwar recession did employers cut base wages to reduce costs. Different combinations of adjustment strategies are apparent, and the particular choices of labour costs adjustments depend substantially on countries' institutional settings.
Keywords: J30; J32; J33; J51; 330; Labour costs; Margins; Demand and credit shocks; Employment; Firm survey; Wage cuts; European Union